Pengaruh komposisi perekat dan diameter briket biopellet terhadap karakteristik dan temperatur pembakaran pada kompor gasifikasi - Tri Cahyo Wahyudi; Sulis Dri Handono; Lukito Dwi Yuono; Rohyani Rohyani (TURBO [Tulisan Riset Berbasis Online], 2021)
Biopellet is a type of solid fuel based on biomass waste which has a smaller size than briquettes. The purpose of this study was to determine the effect of adhesive composition and the effect of the diameter of biopellet briquettes on the characteristics and temperature and combustion time of the gasification stove. The method used was a mixture of 40% sawdust biomass and 60% coconut shell charcoal by varying the adhesive as much as 20%, 25%, 30% on 4 mm and 7 mm diameter biopellet briquettes. Based on the test results, it is known that the adhesive composition affects the temperature and time produced during combustion. The highest temperature reached 713.20C with an adhesive percentage of 20% at a diameter of 7 mm biopellet briquettes with a flash time of 26 minutes. While the lowest temperature reached 653.00C with 30% adhesive percentage on 4 mm diameter biopllet briquettes and 30 minutes of flame time. For the characteristics of biopellet briquettes from laboratory tests, the highest moisture content value was 8.10% in 30% adhesive at 4 mm diameter for the highest ash content value 9.45% at 30% adhesive variation at 4 mm diameter and the highest calorific value reached 4571.64 cal/g of 20% adhesive vari at 7 mm diameter.